2012
DOI: 10.1103/physrevc.85.024908
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the hydrodynamic response to the initial geometry in heavy-ion collisions

Abstract: We investigate how the initial geometry of a heavy-ion collision is transformed into final flow observables by solving event-by-event ideal hydrodynamics with realistic fluctuating initial conditions. We study quantitatively to what extent anisotropic flow (v n ) is determined by the initial eccentricity ε n for a set of realistic simulations, and we discuss which definition of ε n gives the best estimator of v n . We find that the common practice of using an r 2 weight in the definition of ε n in general resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
373
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 316 publications
(393 citation statements)
references
References 89 publications
19
373
0
1
Order By: Relevance
“…(2), with the average taken over all particles in the pseudorapidity interval −1 < η < 1. The procedure used to measure v n in hydrodynamics thus mimics the experimental procedure, with two differences: (i) there is no need for a rapidity gap, because nonflow correlations are negligible; (ii) there is no need for a resolution correction, because the huge multiplicity per event ensures that the resolution is close to 1 for all events [47]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2), with the average taken over all particles in the pseudorapidity interval −1 < η < 1. The procedure used to measure v n in hydrodynamics thus mimics the experimental procedure, with two differences: (i) there is no need for a rapidity gap, because nonflow correlations are negligible; (ii) there is no need for a resolution correction, because the huge multiplicity per event ensures that the resolution is close to 1 for all events [47]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As in Ref. [47], at the end of each hydro event, we run the Monte-Carlo generator many times, so that we can do the flow analysis using approximately 6 × 10 5 particles per event. This significantly reduces statistical noise and allows for an accurate determination of v n and Ψ n in every event.…”
Section: Resultsmentioning
confidence: 99%
“…We found that hcos [2 2 ]i ⇠ 0.99 while hcos [3 3 ]i ⇠ 0.33 in our simulation. It would be interesting to test if there is an analog of the mapping of the eccentricities onto the final high p T flow harmonics that also mirrors the soft correlation seen at low p T [97][98][99].…”
Section: Results For Rmentioning
confidence: 99%
“…The effects of these transport coefficients on the hydrodynamic evolution of the strongly interacting fireball and on various observables in HICRE, e.g. the elliptic flow, spectra of hadronic and electromagnetically interacting particles, etc have been studied extensively [3][4][5][6][7][8]. The general consensus reached is that the matter created in heavy ion collisions behaves almost like a perfect liquid [9][10][11][12][13] with η/s close to the KSS (Kovtun, Son and Starinets) bound [14].…”
Section: Introductionmentioning
confidence: 99%